The Forgotten Songs of the Newfoundland Outports : As Taken from Kenneth Peacock's Newfoundland Field Collection, 1951-1961 - Kearney Guigne, Anna, 1953-; Osborne, Evelyn, 1975-; Peacock, Kenneth (Book collections on Project MUSE., 2016)
"Between 1951 and 1961, the classical composer and pianist Kenneth Peacock (1922-2000) visited the island of Newfoundland six times on behalf of the National Museum of Canada (today the Canadian Museum of History) to collect folksongs. During this period Peacock acquired a total of 766 songs from 118 individuals in 38 communities."